RANCANAGAN ORNAMEN 'MOTIF-MOTIF URBAN' PADA KAIN TENUN NUSANTARA - Dina Martin; Ganal Rudiyanto (Jurnal Dimensi Seni Rupa dan Desain, 2013)
Abstract Indoensia rich in ornaments, motifs and color of clothes weaving. This diversity is the influence of geographical factors, demograraphic and outsider influences. There are several working techniques, the most common technique is the tehnique of ikat weaving lungsi, the second is the technique of feed belt, tie the third is called multiple or double ikat tie. Sumba is one area in Indonesia is rich in decoration of ikat weaving. Researchers used a contructivist the existing motifs on weaving clothes , it used as the basis of creation, the science of aesthetics, science, phenomenology, and the science of design. Urban weaving motifs created by using a phenomenological observation motifs that exist in Sumba ikat, and observations made by researchers observed using the sense and reflect the basis for the creation of urban motifs woven fabric. To create new weaving patterns of urban motifs as the end of the result. AbtrakIndonesia kaya akan ragam hias, motif dan pewarnaan pada kain Nusantara . Keragaman ini merupakan pengaruh dari faktor geografis, demografis dan pengaruh luar. Ada beberapa teknik pengerjaan, teknik yang paling umum adalah teknik ikat lungsi, kedua adalah teknik ikat pakan, ikat yang ketiga adalah yang disebut dengan tenun ikat berganda atau dobel ikat. Sumba merupakan salah satu daerah di Indonesia yang kaya akan ragam hias tenunnya. Peneliti menggunakan pardigma teori filsafat konstuktivisme Guba, secara ontologi, epistomologi dan metodologi.